1999
DOI: 10.1139/e98-037
|View full text |Cite
|
Sign up to set email alerts
|

Lithogeochemistry of volcano-plutonic assemblages of the southern Hanson Lake Block and southeastern Glennie Domain, Trans-Hudson Orogen: evidence for a single island arc complex

Abstract: This paper describes the geology, geochemistry, and age of two amphibolite facies volcano-plutonic assemblages in the southern Hanson Lake Block and southeastern Glennie Domain of the Paleoproterozoic TransHudson Orogen of east-central Saskatchewan. The Hanson Lake assemblage comprises a mixed suite of subaqueous to subaerial dacitic to rhyolitic (ca. 1875 Ma) and intercalated minor mafic volcanic rocks, overlain by greywackes. Similarly with modern oceanic island arcs, the Hanson Lake assemblage shows evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This package, which collectively is termed the Jan Lake Complex, is mantled by an upper amphibolite-facies package of gneisses comprising arc volcanic rocks, derived pelites, and intrusive granodiorites and tonalites. To the south and southeast, this dominantly volcano-plutonic package appears to grade into the less metamorphosed and better known rocks of the Hanson Lake (Maxeiner et al 1999) and Flin Flon areas (e.g., Syme et al 1998), respectively, (Fig. 2), where precise U-Pb age dating has yielded 1920-1870 Ma ages for volcanic rocks and 1870-1830 Ma ages for intrusive granitoids.…”
Section: Regional Geologymentioning
confidence: 99%
“…This package, which collectively is termed the Jan Lake Complex, is mantled by an upper amphibolite-facies package of gneisses comprising arc volcanic rocks, derived pelites, and intrusive granodiorites and tonalites. To the south and southeast, this dominantly volcano-plutonic package appears to grade into the less metamorphosed and better known rocks of the Hanson Lake (Maxeiner et al 1999) and Flin Flon areas (e.g., Syme et al 1998), respectively, (Fig. 2), where precise U-Pb age dating has yielded 1920-1870 Ma ages for volcanic rocks and 1870-1830 Ma ages for intrusive granitoids.…”
Section: Regional Geologymentioning
confidence: 99%
“…The northern volcanic belt consists of the Lynn Lake and La Ronge belts, two island arcs which were active near the Rae-Hearne craton. Following the geological and geochemical analysis of Maxeiner et al [1999], we lump together the volcanic and plutonic rocks of the Glennie domain, the Flin Flon and Snow Lake Belts and their extensions beneath the Paleozoic sedimentary cover into a single southern volcanic belt. This belt was formed at large distance from the northern volcanic belt.…”
Section: Trans-hudson Orogenmentioning
confidence: 99%
“…Temperature gradients in the two holes are identical in the upper 250 m and are perturbed by the neighboring lake. The equilibrium heat flow was determined from the deep part of borehole 9506 where heat [24] These two deep boreholes are located in the southern extent of the Hanson Lake block in the Flin Flon belt [Leclair et al, 1997;Maxeiner et al, 1999] where Archean basement windows are identified [Ashton et al, 1999]. They penetrate sequences of schists interlayered with gabbros and basalts.…”
Section: Southern Margin At the Edge Of The Paleozoic Covermentioning
confidence: 99%
“…Volcano-plutonic complexes are important geological units that typically occur in arc and back-arc settings (Beiersdorfer 1993;Maxeiner et al 1999;Imaoka and Itaya 2004). Western Turkey is a part of the Alpine-Himalayan orogenic belt in which continental collision and subsequent extension have resulted in the development of successive, overlapping magmatic belts beginning in the Eocene.…”
Section: Introductionmentioning
confidence: 99%